Effect of storage atmosphere and temperature on the oxidative stability of almond kernels during long term storage. (May 2015) - Raisi, Marzieh; Ghorbani, Mohammad; Sadeghi Mahoonak, Alireza; Kashaninejad, Mahdi; Hosseini, Hamed
Abstract: In this study, the oxidative stability of almonds (Var. Mamaei) stored for a period of 10 months was examined. The influence of temperature (ambient and refrigeration), type of atmosphere (vacuum, CO2 and normal air) and the product physical shape (whole kernels and ground) on the oxidation stability were studied under conditions of darkness. Peroxide value (PV) and conjugated trienes (K268 ) were used as indicators for oxidation progress. Odor and flavor were also used for sensory evaluation. According to the results, effects of differing temperature, type of atmosphere or physical shape on PV and K268 were significantly different ( P  < 0.05). At the end of storage with PV of 3.41 meqO2 /kg and K268 of 3.42 μmol/g the ground almond sample exposed to air at ambient temperature was the least stable, and the whole kernels under vacuum kept in a refrigerator at 4 °C with PV of 0.69 meqO2 /kg and K268 of 0.63 μmol/g were the most stable form against oxidation. As a result, with regard to PV, unpacked whole kernels and ground almonds stored at ambient temperature remained fresh for 8–9 and 7 months of storage, respectively, while the same samples in refrigeration had shelf lives above 10 months. The use of modified atmosphere packaging under vacuum and CO2 provided a shelf life of at least 10 months for all samples irrespective of storage temperature and physical shape of the nuts. Thus modified atmosphere packaging was a most effective method for protecting the almonds from oxidation. Highlights: Storing whole kernels rather than ground almonds is advised for long term storage. MA storage is an effective method for protecting the almonds from oxidation. It is recommended to package almonds under vacuum or CO2 to increase shelf life. Refrigeration or MA storage are essential to maintain the quality in almonds.